Targeted disruption of S100P suppresses tumor cell growth by down-regulation of cyclin D1 and CDK2 in human hepatocellular carcinoma - Kim, Jeong Kyu; Jung, Kwang Hwa; Noh, Ji Heon; Eun, Jung Woo; Bae, Hyun Jin; Xie, Hong Jian; Ahn, Young Min; Ryu, Jae Chun; Park, Won Sang; Lee, Jung Young; Nam, Suk Woo (SPANDIDOS PUBL LTD, 2009)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide. The number of cases of HCC has continued to increase in recent decades. Previous studies have suggested that S100P, a member of the S100P calcium-binding protein family, is aberrantly regulated in several malignant neoplasms. However, the underlying molecular mechanisms of the dysregulation of S100P remain to be elucidated. To investigate biological effects of S100P on hepatocarcinogenesis, aberrant expression of S100P was investigated by immunohistochemistry (IHC), Western blot analysis and reverse transcriptase-polymerase chain reaction (RT-PCR) in HCC tissues and cell lines. Endogenous expression of S100P was disrupted by the RNA interference-mediated protein knockdown method in the human Hep3B liver cancer cell line. Then, cell growth and cellular apoptosis were compared with control siRNA transfectants. The effects of S100P-silencing on the major components of cell cycle regulation were assessed by Western blot analysis. As results, elevated levels of S100P were observed in the HCC tissues compared to the corresponding normal tissues. Targeted disruption of S100P suppressed cell growth and augmented cellular apoptosis. In addition, inhibition of S100P resulted in the down-regulation of cyclinD1 and CDK2. In conclusion, this study showed over-expression of S100P in HCC. The aberrant regulation of S100P in HCC might activate cyclin D1 and CDK expression and contribute to the mitogenic potential of tumor cells during HCC carcinogenesis. These findings provide information that suggests new therapeutic strategies for the treatment of liver cancer.
Keywords: DIFFERENTIAL GENE-EXPRESSION; CANCER; SURVIVAL; FAMILY; ADENOCARCINOMA; PURIFICATION; METASTASIS; MUTATIONS; PROTEINS; COLON